Zambia : Poverty Reduction Strategy Paper Second Annual Progress Report-Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2005)
This Joint Staff Advisory Note (JSAN) focuses on the Second Annual Progress Report for Zambia's Poverty Reduction Strategy Paper (PRSP). The government's strategy to reduce poverty focuses on promoting economic growth through macroeconomic stabilization and diversification and improving the quality of service delivery, while addressing crosscutting issues of governance, HIV/AIDS, gender, and the environment. The JSAN provides IMF staff advice on priorities for advancing the PRSP implementation. It highlights progress in implementing the PRSP and provides suggestions for strengthening its implementation. The risks associated with implementation are also described.